Understanding the accessibility to urban green spaces: Lisbon Case Study - Silva, Beatriz Isabel da Luz (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence